PENEGAKAN HUKUMKEIMIGRASIAN TERHADAP KEJAHATAN YANG TERJADI KEPADA PEKERJAMIGRAN INDONESIADALAM PERSPEKTIF KRIMINOLOGI KRITIS - Bakhtiar, Masdar; Sari, Mita Apriyana (Polteknik Imigrasi, 2023)
Indonesian migrant workers (PMI) are a group that is vulnerable to various risks and crimes during their migration process. Immigration law enforcement in this context is important in protecting the rights and security of PMI. Immigration law enforcement regarding crimes that occur to PMI by viewing them from a critical criminology perspective. The critical criminology approach views human trafficking and immigration-related crimes as complex phenomena influenced by social, economic, and political factors. This journal discusses criminological factors that influence PMI, including economic and social conditions, recruitment and visa systems, working conditions, and inequalities in access to the legal system. In the context of immigration law enforcement, this Journal highlights the possible impacts including criminalization of victims, increased risk, control and domination, as well as a lack of legal alternatives. In striking a balance between law enforcement and human rights protection, this journal raises questions about the effectiveness and fairness of legal responses to immigration crimes. In conclusion, immigration law enforcement against crimes that occur to PMI needs to be seen in a broader context, considering criminological factors and human rights. A holistic and welfare-oriented approach in dealing with this complex problem, by prioritizing the protection and rights of PMI in their migration process